Letter from Lewis H. Gause to James Curtis Booth - Gause, Lewis H. (1832)
Lewis H. Gause, a student, explains to his professor, James Curtis Booth (1810-1888), that he is financially constrained from continuing his studies in chemistry with Booth.
Keywords: Booth, James Curtis, 1810-1888; Chemistry--Study and teaching; Chemistry teachers; Chemistry